Optimizing Public Policy Evaluation: Utilization of Data and Evidence-Based Approaches in the Evaluation of the Sunan Kuning Semarang Closure Policy - Yuliani, Isnaeni; Larasati, Endang; Kismartini, Kismartini; Yuniningsih, Tri (Indonesian Association for Public Administration (IAPA), 2024)
Five years have passed since the closure of Sunan Kuning, yet it has left various residual problems that are not only related to moral issues alone but also linked to economic, health, and social structures. This study aims to provide a comprehensive overview of the evaluation of the Sunan Kuning Semarang red-light district closure policy. The policy evaluation model used was the Countenance model by Robert E. Stake (2004), which divided policy evaluation into three stages: (1) antecedent; (2) transactions; and (3) outcome. The approach utilized in this research was qualitative. The author used a purposive sampling technique. Information gathering was conducted through semi-structured, in-depth interviews, as well as interviews with experts. Additionally, information was also gathered through observation, document analysis, and literature review. The analysis technique involved three components: data reduction, data display, and drawing and testing conclusions. From the research results, the researcher concluded that the closure policy of the Sunan Kuning district has not been optimal. As recommendations, several key elements such as the government's political will in executing each policy process. Additionally, recommendations from previous research considerations and aspects of previous policy experiences need to be considered in policymaking.